Kajian Nilai Daya Dukung Tanah Lempung Merah Dengan Bahan Tambah Kapur Melalui Uji CBR - Triwardaya, Triwardaya; Pawiro, Dadiyono Amat; Ukiman, Ukiman; Sutarno, Sutarno (Politeknik Negeri Semarang, 2015)
Soil materials that the grain size of the composition can comprise coarse material (gravel, sand) and fine materials (silt and clay). At the material / soil materials that include fine-grained soil that contains granules ø 0.075 mm over 50% will be dominated by clay content. This material will have a high value of plasticity and low power as well as developing a sizeable shrinkage. Lime that has binding properties (lime stone) when added to the material clay changes will provide both improved quality, bulk density, as well as lime-enabled so the added material on clay red around POLINES as filler material (filter) with different variations in the mix and treatment peneraman and soaking would boost its strength tested by the carrying capacity by means of CBR (California Bearing Ratio) test results in the laboratory value of CBR plans on condition brooded until 7 days: CBR its 2.4 kp + 20.8 with a level of correlation R = 0.9328 , And soaked conditions until 7 days: his CBR kp 4.4 - 0.8 with a degree of correlation R = 0.9874.